Pergeseran Pemikiran Nurcholish Madjid Tentang Partai Politik Islam Di Indonesia - Jun Mawalidin Jun (Politica: Jurnal Hukum Tata Negara dan Politik Islam, 2022)
Abstract In this study, researchers conducted a study on nurcholish madjid thought known as Nurcholisisme which is said to be very critical of Islamic political parties in Indonesia. That in Nurcholish Madjid's thoughts about Islamic political parties according to him Islam is not an ideology that must exist in the form of a formal institution that is an Islamic party. Islam should be the basis or basis in determining ethical values in running a political party without having to make it in the form of a formal institution. It is an obligation and truth and regards modernization as an effort or process to achieve the truth that is put forward to encourage Muslims to direct their commitment to Islamic values, not to institutions that use the name Islam. In this researched work the author uses legal research normatively towards policy with conceptual approaches and rules. This research was conducted by looking at literature studies to see Nurcholish's thinking aimed at forming a good Islamic party for society. The Islamic party of his time said that they were the representation of the voice of God as the ticket to good. Keywords: Islamic Party, Nurcholish Madjid, Ideology, Politics.